Efficient Colon Cancer Immunogene Therapy Through Co-Delivery of IL-22BP mRNA and Tumor Cell Lysate by CLSV Nanoparticles [Retraction] - Huang J; Wang K; Fu X; Zhu M; Chen X; Gao Y; Ma P; Duan X; Men K (International Journal of Nanomedicine)
Huang J, Wang K, Fu X, et al. Int J Nanomedicine. 2023;18:8059—8075. We, the Editors and Publisher of the International Journal of Nanomedicine, have retracted the published article. Since publication, concerns have been raised by a third party about the integrity of the data in the article, including alleged image duplications in Figures 5 and 6 of the article. The authors then contacted the Journal requesting a correction of the article. Following an investigation, the Journal and Publisher confirm that Figures 2, 5 and 6 include duplicated image panels which affect the integrity of the reported results. As verifying the validity of published work is core to the integrity of the scholarly record, we are therefore retracting the article. The corresponding author listed in this publication has been informed. We have been informed in our decision-making by our editorial policies and the COPE guidelines. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as ‘Retracted’.